Anti-apoptotic gene Bcl2 is required for stapes development and hearing - Carpinelli, Marina; Wise, Andrew; Arhatari, Benedicta; Bouillet, Phillipe; Manji, Shehnaaz; Manning, Michael; Cooray, Anne; Burt, Rachel (Macmillan Publishers Limited, 2012)
In this paper we describe novel and specific roles for the apoptotic regulators Bcl2 and Bim in hearing and stapes development. Bcl2 is anti-apoptotic while Bim is pro-apoptotic. Characterization of the auditory systems of mice deficient for these molecules revealed that Bcl2 / mice suffered severe hearing loss. This was conductive in nature and did not affect sensory cells of the inner ear, with cochlear hair cells and neurons present and functional. Bcl2 / mice were found to have a malformed, often monocrural, porous stapes (the small stirrup-shaped bone of the middle ear), but a normally shaped malleus and incus. The deformed stapes was discontinuous with the incus and sometimes fused to the temporal bones. The defect was completely rescued in Bcl2 / Bim / mice and partially rescued in Bcl2 / Bimþ/ mice, which displayed high-frequency hearing loss and thickening of the stapes anterior crus. The Bcl2 / defect arose in utero before or during the cartilage stage of stapes development. These results implicate Bcl2 and Bim in regulating survival of second pharyngeal arch or neural crest cells that give rise to the stapes during embryonic development.
Publisher's link to article: http://www.nature.com/cddis/journal/v3/n8/full/cddis2012100a.html
Keywords: Hearing; Mouse; Gene; Stapes; Hearing Development; Apoptosis; BCL2; Hair Cells